Elevated SNRPA1, as a Promising Predictor Reflecting Severe Clinical Outcome via Effecting Tumor Immunity for ccRCC, Is Related to Cell Invasion, Metastasis, and Sunitinib Sensitivity - Jiang, Aimin; Meng, Jialin; Gong, Wenliang; Zhang, Zhonghua; Gan, Xinxin; Wang, Jie; Wu, Zhenjie; Liu, Bing; Qu, Le; Wang, Linhui (Frontiers in Immunology, 2022)
Clear cell renal cell carcinoma (ccRCC) is the most common subtype of renal carcinoma and is associated with poor prognosis and notorious for its immune dysfunction characteristic. SNRPA1 is a spliceosome component responsible for processing pre-mRNA into mRNA, while the biological effect of SNRPA1 in ccRCC remains elusive. The aim of this study was to decipher the effect of SNRPA1 on clinical effect and tumor immunity for ccRCC patients. Multi-databases were collected to evaluate the different expression, prognostic value, DNA methylation, tumor immune microenvironment, and drug sensitivity of SNRPA1 on ccRCC. IHC was utilized to validate the expression and prognostic value of SNRPA1 in ccRCC patients from SMMU cohort. Knockout expression of SNRPA by sgRNA plasmid inhibited the cell proliferation, migration and metastasis ability, and significantly increased the sensitivity of Sunitinib treatment. In addition, we explored the role of SNRPA1 in pan-caner level. The results indicated that SNRPA1 was differentially expressed in most cancer types. SNRPA1 may significantly influence the prognosis of multiple cancer types, especially in ccRCC patients. Notably, CCNA2 was significantly correlated with immune cell infiltration and immune checkpoint inhibitory genes. In addition, the aggressive and immune inhibitory effect showed in SNRPA1 over-expression, and effect of SNRPA1 on ccRCC cell lines invasion, metastasis and drug sensitivity in vitro were observed. Moreover, SNRPA1 was related to Myc, MTORC, G2M, E2F and DNA repair pathways in various cancer types. In all, SNRPA1 may prove to be a new biomarker for prognostic prediction, effect tumor immunity and drug susceptibility in ccRCC.